Small heat shock protein αB‐crystallin potentiates Aβ neurotoxicity by hetero‐oligomeric stabilization. (1st February 2022) - Moncaster, Juliet A; Zhang, Xiao‐Lei; Gangalum, Rajendra; Sullivan, John; Zeldich, Ella; Chen, Cidi; Sarangi, Srikant; Minaeva, Olga; Altman, Robin; Alvarez, Victor E.; Huber, Bertrand R.; McKee, Ann C.; et al.
Abstract: Background: Amyloid plaque, a neuropathological hallmark of Alzheimer's disease (AD), is composed of neurotoxic amyloid‐β (Aβ) peptides and other proteins, including the small heat shock protein αB‐crystallin (also known as HSPB5). We investigated the cellular origin of αB‐crystallin, its secretion properties and how it may affect formation of neurotoxic Aβ hetero‐oligomers. Method: Immunohistofluorescence, Confocal Microscopy, Immunogold electron microscopy, SDS‐page and immunoblotting, electron paramagnetic resonance spectroscopy (EPR), quasi‐elastic light scattering (QLS) spectroscopy, cell and organotypic slice culture, LDH and propidium iodide assays. Result: Immunohistofluorescence analysis of human AD brain revealed that Aβ and αB‐crystallin co‐localize in extracellular dense core and diffuse plaques and in surrounding reactive astrocytes. Immunohistochemical and immunoblotting analyses showed that astrocytes secrete αB‐crystallin in vitro via an exosomal pathway. Co‐incubation of αB‐crystallin and Aβ suppressed Aβ fibrillogenesis by sequestration in hetero‐oligomeric complexes however, this resulted in αB‐crystallin potentiated Aβ neurotoxicity in mouse primary neurons and organotypic rat hippocampus slice culture as revealed by LDH and Propidium Iodide assays. Moreover, αB‐crystallin acutely potentiated Aβ‐induced impairment of activity‐dependent long‐term potentiation (LTP) of rat Schaffer collateral‐CA1 synaptic transmission. Conclusion: These results indicate that the small heat shock protein αB‐crystallin is secreted by reactive astrocytes and potentiates Aβ neurotoxicity by stabilizing hetero‐oligomers.